Assessment of Small and Medium Enterprises´ Using Market Analytics for Logistics Companies - Dasan, Pramod (2014)
This thesis aims to focus on the determinants influencing the internationalization of small and medium-sized enterprises (SMEs) in Brazil, Russia, India, China, Mexico and Czech Republic (BRICM + CZ -- emerging markets). The objective is to investigate and evaluate the business environment and, then, examine the importance of developing and promoting entrepreneurship to allow SMEs in above selected countries to develop a competitive position in the international marketplace. An overview is provided of the current economic situation faced by SMEs in those emerging markets. Then factors necessary for the expansion of the business will be discussed, along with the challenges of overcoming the resource gaps to be identified. The results are based on empirical surveys along with the use of statistical software tools to predict the potential of revenue growth in SME sector. Information is provided concerning the current situation for SMEs in those countries and the challenges encountered as they face a business environment that is becoming more competitive. We also found that SMEs are increasingly more integrated to global economy and not limited to regional/international activities. Quantitative analysis shows that there is significant potential for SME for next couple of year despite economic uncertainty. This thesis integrates entrepreneurship, and the resource-based internationalization of SMEs in developing markets specifically focusing on the use of technology.